How Does The Covid-19 Pandemic Impact On The Training Patterns Of Indonesian Sitting Volleyball Athletes? - Prayogi Dwina Angga; Deddy Whinata Kardiyanto (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine the impact of the COVID-19 pandemic on the training patterns of seated volleyball athletes for the Indonesian national team. All members of the Indonesian seated volleyball national team participated in filling out a questionnaire consisting of sports participation, exercise intensity and volume, the impact of COVID-19 on exercise patterns, and training support infrastructure. A total of 11 athletes who were all male with an average age of 31.91 (± 7.43) had completed the questionnaire in the period July to August 2020. Most of the athletes practiced 5 times per week (73%) which was carried out in the morning and evening. in the afternoon (36%), they do exercises with direct guidance from online trainers both synchronously and asynchronously (82%). Athletes also feel that they experience a reduction in exercise volume and intensity (45%) compared to when they were at the national training center. Most athletes (82%) felt that they had experienced a decline in their physical condition. it is very clear that the COVID-19 pandemic is having a huge impact on the training patterns of seated volleyball athletes, they must focus more on maintaining their training to maximize their fitness so that they perform optimally when competition resumes.